KAJIAN KETAHANAN BANK UMUM SYARIAH: STUDI PEMETAAN DAN TINJAUAN SISTEMATIK LITERATUR - Wiranatakusuma, Dimas Bagus; Alivia Mufiddatul Aryanti (Nusantara Hasana Journal, 2025)
This study aims to analyze trends and identify research gaps on the resilience of Islamic banking using 23 studies in the period 2019–2023. The methods used are systematic literature review and mapping study. The results of the analysis show that the majority of studies discuss the influence of the financial crisis, economic uncertainty, internal banking financial indicators and macroeconomics on the stability of Islamic banks. The regression method is the dominant approach in testing the relationship between variables, while some other studies apply the Early Warning System (EWS) to detect banking risks. However, there are several gaps in the literature that need to be considered in further research. First, many studies only focus on the analysis of Islamic banking resilience using net Non-Performing Financing (NPF) without considering its impact on certain economic sectors. Second, most studies only evaluate the significance of variables on banking resilience without calculating the optimal level of each indicator in the current economic context. Therefore, a more comprehensive approach is needed with an analysis model that is able to measure the optimal balance between risk and profitability of Islamic banking. Future research is also suggested to adopt a dynamic approach that considers the variability of economic conditions and integrates technology into the Islamic banking system to increase its resilience to both internal and external shocks.